Effects of a convertible to-and-fro and circle anesthetic system on cardiopulmonary variables in isoflurane anesthetized horses - Natalini, Claudio Corrêa; Polydoro, Alexandre da Silva; Cavalcanti, Ruben Lundgren; Branquinho, Luciana Queiroga; Crosignani, Nadia; Serpa, Priscila Beatriz; Schallenberger, Rodrigo Gonçalves; Molnar, Bruna Favieiro Pellin de; Carregaro, Adriano; Futema, Fábio (Acta Scientiae Veterinariae, 2018)
Six healthy adult horses two male and four female, mean body weight of 424 + 44.1kg, were anesthetized with xylazine, ketamine/diazepam and isoflurane for 60 minutes using a convertible to-and-fro and circle system. Variables analyzed were arterial blood pH, carbon dioxide partial pressure (PaCO 2) and oxygen partial pressure (PaO2), respiratory rate(RR), and blood pressure. The horses were allowed to breath spontaneously, and were positioned in right lateral recumbency. The arterial O2 values were significantly higher during isoflurane anesthesia when compared to the baseline values, and significantly lower after induction with ketamine/diazepam although arterial hypoxemia were not present. The arterial PCO2 values were significantly higher from baseline values during isoflurane anesthesia occurring arterial hypercapnia and mild respiratory acidosis. The arterial pH changes paralleled the changes in PaCO 2. Respiratory rate values were significantly lower during isoflurane anesthesia when compared to baseline values. All values remained within accepted range for lateral recumbent spontaneously breathing anesthetized horses. There were no significant differences between the circle and the to-and-fro system, demonstrating that either system is safe to maintain isoflurane anesthesia in adult horses.